2019
DOI: 10.4103/ijo.ijo_841_19
|View full text |Cite
|
Sign up to set email alerts
|

Coats disease: An overview of classification, management and outcomes

Abstract: Coats disease is an idiopathic retinal vascular disorder with retinal telangiectasia with intraretinal and/or subretinal exudation without appreciable retinal or vitreal traction. The condition is sporadic with no associated systemic abnormalities. Unilateral involvement in young males is the typical presentation with most cases being diagnosed in the first and second decade of life. Younger the patient, more severe is the presentation and poorer the visual outcome. The management varies with the stage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 52 publications
0
41
0
17
Order By: Relevance
“…Diagnosis of Coats' disease should not be accepted in an adult until other causes of exudative retinopathy are clearly excluded. 1 Although ERM in Coats' disease (both juvenile and adult-onset) is a rare entity, it might cause significant visual acuity loss in these patients. 1 Its exact pathogenesis is not known, but it develops secondary to excessive retinal photocoagulation or cryoretinopexy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diagnosis of Coats' disease should not be accepted in an adult until other causes of exudative retinopathy are clearly excluded. 1 Although ERM in Coats' disease (both juvenile and adult-onset) is a rare entity, it might cause significant visual acuity loss in these patients. 1 Its exact pathogenesis is not known, but it develops secondary to excessive retinal photocoagulation or cryoretinopexy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although ERM in Coats' disease (both juvenile and adult-onset) is a rare entity, it might cause significant visual acuity loss in these patients. 1 Its exact pathogenesis is not known, but it develops secondary to excessive retinal photocoagulation or cryoretinopexy. 7 Shields et al in their study of 150 patients with juvenile and adult-onset Coats' disease found ERM in 2.5 % of treated eyes with poor visual outcomes [1], while Rishi et al reported a higher incidence of ERM (4.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Häufig liegen auch subretinale Exsudationen, Makulaödeme und Blutungen vor [14]. Dies resultiert in einer erheblichen Visusbeeinträchtigung und, da der Erkrankungsbeginn früh ist, in einer tiefen Amblyopie.…”
Section: Klinik Diagnostikunclassified